An Experimental Investigation Devoted to Determine Heat Transfer Characteristics in a Radiant Ceiling Heating System - Koca, Ali İhsan; Açıkgöz, Özgen; Çebi, Alican; Çetin, Gürsel; Dalkılıç, Ahmet Selim; Wongwises, Somchai (Springer, 2017)
Investigations on heated ceiling method can be considered as a new research area in comparison to the common wall heating-cooling and cooled ceiling methods. In this work, heat transfer characteristics of a heated radiant ceiling system was investigated experimentally. There were different configurations for a single room design in order to determine the convective and radiative heat transfer rates. Almost all details on the arrangement of the test chamber, hydraulic circuit and radiant panels, the measurement equipment and experimental method including uncertainty analysis were revealed in detail indicating specific international standards. Total heat transfer amount from the panels were calculated as the sum of radiation to the unheated surfaces, convection to the air, and conduction heat loss from the backside of the panels. Integral expression of the view factors was calculated by means of the numerical evaluations using Matlab code. By means of this experimental chamber, the radiative, convective and total heat-transfer coefficient values along with the heat flux values provided from the ceiling to the unheated surrounding surfaces have been calculated. Moreover, the details of 28 different experimental case study measurements from the experimental chamber including the convective, radiative and total heat flux, and heat output results are given in a Table for other researchers to validate their theoretical models and empirical correlations.
Keywords: Radiant Heating; Radiant Systems; Hydronic Radiant Ceiling System; Experimental Chamber; Heat Transfer